Which infants need lumbar puncture (LP) for suspected serious bacterial infection?. Issue 7 (July 2017) - Neff, Laurel; Pickett, Jonathan
Abstract : EVIDENCE‐BASED ANSWER : The evidence is unclear. Comparison of the Boston, Philadelphia, Milwaukee, and Rochester protocols for serious bacterial infection (SBI) in infants showed no protocol was superior to another (SOR: A, meta‐analysis of prospective and retrospective studies). C‐reactive protein (CRP) is the most accurate individual laboratory value for ruling out SBI in an infant younger than 90 days (SOR: A, meta‐analysis of prospective and retrospective studies). Clinical guidelines support LP in febrile infants <28 days old, but may not be indicated for age >29 days if they meet low‐risk criteria (SOR: C, opinion, clinical guideline).